Tuberculosis epidemiological trend in Sousse, Tunisia during twenty years (2000–2019). Issue 1 (1st January 2022) - Melki, Sarra; Mizouni, Ghodhbani; Chebil, Dhekra; Ben Abdelaziz, Ahmed
ABSTRACT: Describe the epidemiology of tuberculosis in the last two decades (2000–2019) in the East region of Tunisia (city of Sousse). This was a descriptive retrospective analysis of notified incident cases of tuberculosis from 2000 to 2019 in Sousse Governorate, Tunisia. The data collection was done via the regional registry of tuberculosis. Stata software was used to characterize the socio-demographic and clinical profile of tuberculosis, to calculate its incidence, mortality and fatality rates and to determine predictive factors of mortality. R software was used to analyze the chronological trend of tuberculosis incidence and mortality. A total of 2606 incident cases of tuberculosis were declared from 2000 to 2019 in Sousse. The mean age was 39 ± 19 years with a sex ratio (male/female) of 1.19. Only one case was HIV positive among the total 2606 incident cases. Extra-pulmonary tuberculosis was the most recorded (1, 534 cases, 58.9%). The mean annual case notification and deaths were 130 and four respectively. After adjusting for confounders, individuals with pulmonary tuberculosis were 1.9 significantly more likely to die from tuberculosis compared to those suffering from extra-pulmonary tuberculosis. There was a trend of increasing mortality with increasing age. The association was statistically significant only for those above 60 years' old who had 12.5 times higher odds of dying compared to those below 60 years. After adjusting for age and gender, with every year there was an increase in the total incidence rate (+0.35 per 100, 000) with p = 0.005 and in the extra-pulmonary incidence (+0.27 per 100, 000), with p = 0.001. This study demonstrated the increasing trend of tuberculosis in Sousse, Tunisia from 2000 to 2019. The national program against tuberculosis should enhance community knowledge and centralize the national and regional epidemiological information for better epidemiological surveillance.